2015
DOI: 10.1016/j.bbmt.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Management, and Outcome of Invasive Fungal Disease in Patients Undergoing Hematopoietic Stem Cell Transplantation in China: A Multicenter Prospective Observational Study

Abstract: The China Assessment of Antifungal Therapy in Hematological Disease study, the first large-scale observational study of invasive fungal disease (IFD) in China, enrolled 1401 patients undergoing hematopoietic stem cell transplantation (HSCT) (75.2% allogeneic and 24.8% autologous) at 31 hospitals across China. The overall incidence of proven or probable IFD was 7.7% (108 of 1401); another 266 cases (19.0%) were possible IFD. After allogeneic or autologous HSCT, the incidence of proven/probable IFD was 8.9% (94 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 25 publications
6
78
0
6
Order By: Relevance
“…The incidence of invasive fungal infection (IFI) has been reported at 9% after allogeneic HCT; some studies show an increase in fungal infection with matched unrelated donor compared to matched related donor. 14,15,16 . In a study of 1400 patients in China, mortality was over 30% in patients with proven IFI 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of invasive fungal infection (IFI) has been reported at 9% after allogeneic HCT; some studies show an increase in fungal infection with matched unrelated donor compared to matched related donor. 14,15,16 . In a study of 1400 patients in China, mortality was over 30% in patients with proven IFI 15 .…”
Section: Introductionmentioning
confidence: 99%
“…14,15,16 . In a study of 1400 patients in China, mortality was over 30% in patients with proven IFI 15 . Bacterial infections, especially after UCBT, are associated with high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Girmenia et al7 investigated the epidemiology of IFI in a cohort of 1858 allogeneic HSCT recipients showing that grafts from an unrelated donor or umbilical cord blood were associated in multivariate analysis with a high risk of early IFI occurring before day 40. Similarly, Sun et al8 demonstrated that the cumulative incidence of IFI in autologous HSCT patients, recipients of HLA-matched related, haploidentical, and unrelated HSCT was 3.5%, 4.3%, 13.2% and 12.8% respectively.…”
Section: Introductionmentioning
confidence: 84%
“…In particular, pretransplantation DM significantly increased the risk of invasive fungal diseases [20][21][22]. The mechanism is unclear, but increased risk may be due to impaired neutrophil function in patients with DM [23,24].…”
Section: Pretransplantation Assessment and Interventionmentioning
confidence: 97%